Sistem Monitoring Jumlah Parkir Berbasis Internet Of Things (IOT) di Manado Town Square 3 - Arje Djamen; Fitriani Mustafah Mustafah (Program Studi Teknik Informatika, 2023)
Currently, the parking system only uses conventional parking arrangements with parking lots and officers watching every vehicle that enters Manado Town Square 3. So that long traffic jams often occur due to a lack of information on empty parking lots, especially four-wheeled vehicles. This is due to the absence of a parking monitoring system in Manado Town Square 3 in real time. In this regard, the researchers developed an Internet of Things (IOT) based parking number monitoring system that can facilitate admins in parking monitoring and make it easier for users to check the amount of parking in real time. In this study using the Research & Development (R&D) research method and the Extreme Programming (XP) development method which consists of planning, design, coding, and testing. The results of the study are that sensors can be used to detect incoming and outgoing vehicles that are connected to a system. This is proven by sensors that can detect incoming and outgoing vehicles using 2 entry sensors and 2 exit sensors connected to a monitoring system that can be accessed by admins and users. And based on the test results using blackbox testing. So it can be concluded that the application has been able to run in accordance with their respective functions and procedures.